Studi Pengaman Busbar Pada Gardu Induk Amlapura - Purnawan, I Made Dian; Arjana, I G Dyana; Rinas, I W (Jurnal Teknologi Elektro, 2016)
Busbar safety is a protection system that plays an important role in securing the disruption of the busbar itself. This protection system should work in a sensitive, selective, rapid, and must be stable to disturbance outside the region busbar protection. At the substation Amlapura, if one busbar impaired or absence of the busbar securing safety as on the other substation, will lead to an imbalance perceived by the system and can lead to continuity of power flow can be disrupted. Based on the calculations that have been done shows that for short circuit simulation results busbar A and B obtained Amlapura substation fault current that occurs in the amount of 5.538 kA. For the calculation of the impedance zone 1 (80%) primer is 1.9721 + 5.715 ? A Zsekunder with a time delay of 0 seconds or work instantly, Zone 2 (120%) primer is 5.55 ? Z + J 16.0836 primary, Zone 2 (120%) the secondary is 2.958 + J 8.5726 ? Zsekunder with a time delay of 0.4 seconds. Keywords: Busbar, Rele, Short Circuit Analysis, impedance   DOI: 10.24843/MITE.1501.07